PENGASUHAN BERBASIS KEKUATAN KARAKTER DAN KETERLIBATAN DIRI PADA MAHASISWA - Marissa Chitra Sulastra; Vida Handayani (Faculty of Psychology, Universitas Semarang, 2020)
The purpose of this research is to get a correlation between strength-based parenting (SBP) and engagement among college students. The background of this research is the importance of engagement in college. Engagement is known as human adaptive functioning in their life. Engagement is important because it can help college students to direct their efforts and complete assignments seriously. It is necessary to have proper parenting practiced by parents through the application of positive psychology parenting, based on the strengths of college students (SBP) so that students accustomed to using their strengths and they can do their duties in daily life optimally. Hopefully, they ll become more engaged in carrying out their duties as a college student. The benefits of this research can help college students, parents and educators work together in helping college students get engaged with their studies. This research was conducted on 158 students of the Faculty of Psychology University X. The method used in this research is the correlation method. The survey technique was carried out to collect data. Based on this research, the correlation test s result is r = 0.402, p = 0,000 = < 0.001 which means there is a significant positive correlation between SBP and engagement.Key Words: Strength-based Parenting (SBP), Engagement, Correlation